2015
DOI: 10.1097/brs.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Surgeon Experience and Complication Rates in Adult Scoliosis Surgery

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
2
10
0
1
Order By: Relevance
“…In contrast to previous research on SSI, which generally focused on a wide variety of spinal procedures (e.g., instrumented fusion surgery) and diseases (e.g., spinal trauma and spinal tumor) [ 2 , 8 , 9 ], this study included only the patients with SSI following specific types of procedures and diseases (i.e., lumbar laminectomy and/or herniotomy for degenerative diseases) without metal implants. Second, this study did not account for several factors, including experience level of the surgeon [ 34 ] and malnutrition [ 3 ], which were described as risk factors for SSI in some studies. Although the measured confounders were adjusted by a multivariate analysis, the results may still be biased because of unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous research on SSI, which generally focused on a wide variety of spinal procedures (e.g., instrumented fusion surgery) and diseases (e.g., spinal trauma and spinal tumor) [ 2 , 8 , 9 ], this study included only the patients with SSI following specific types of procedures and diseases (i.e., lumbar laminectomy and/or herniotomy for degenerative diseases) without metal implants. Second, this study did not account for several factors, including experience level of the surgeon [ 34 ] and malnutrition [ 3 ], which were described as risk factors for SSI in some studies. Although the measured confounders were adjusted by a multivariate analysis, the results may still be biased because of unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 study has looked at surgeon experience in relation to SSI, with Skovrlj et al 84 finding that in adult scoliosis surgery, candidate members as compared with active members for the Scoliosis Research Society had a 2-fold increase in the rate of superficial, though not deep, SSI which was statistically significant. In regards to the effect of resident involvement and experience, 3 studies looking at different aspects of this have found an association with SSI.…”
Section: Surgery-associated Risk Factorsmentioning
confidence: 99%
“…The risk of intraoperative complications declined with increasing surgical experience. Skovrlj et al9 evaluated surgeon experience for perioperative complications in patients who underwent adult scoliosis surgery. The incidence of spinal cord complications and surgical site infection seemed to be different between the candidate members and active members of the Scoliosis Research Society.…”
Section: Discussionmentioning
confidence: 99%